Secondary carpal tunnel syndrome caused by an occult ganglion cyst in the carpal tunnel: a case report - Alfallaj, Muath Ibrahim (International Journal of Research in Medical Sciences, 2025)
Carpal tunnel syndrome (CTS) is the most common peripheral compressive neuropathy that begins with pain and sensory symptoms initially and eventually leads to motor impairment. Most cases of CTS are primary (idiopathic), but space-occupying lesions in the carpal tunnel can occasionally be the cause. This article presents a case wherein an occult ganglion cyst caused secondary carpal tunnel syndrome in a 29-year-old female patient. The patient had complained of left index and middle finger pain, numbness, and weakening for five months. Clinical examination revealed positive Phalen’s test and Tinel’s sign in the left hand with hypoesthesia over the palmar side of the index and middle fingers. Nerve-conduction studies of the median nerve revealed a prolonged median to abductor pollicis brevis (APB) distal latency (4.9 m/s). Ultrasonography was suggestive of a ganglion cyst in the left carpal tunnel. Under local anesthesia, an open release of the left carpal tunnel with ganglion excision was effectively performed, and the symptoms were alleviated. It was concluded that space-occupying lesions should be ruled out in patients with carpal tunnel syndrome who do not have any known risk factors.